Characteristics and hotspots of the 50 most cited articles in the field of pre-psoas oblique lumbar interbody fusion - Lin, Guang-Xun; Chen, Chien-Min; Jhang, Shang-Wun; Zhu, Ming-Tao; Lyu, Pengfei; Hu, Bao-Shan (Frontiers in Surgery, 2022)
Purpose: In the past decade, the field of pre-psoas oblique lumbar interbody fusion (OLIF) has developed rapidly, and with it, the literature on OLIF has grown considerably. This study was designed to analyze the top 50 articles in terms of the number of citations through bibliometric research to demonstrate the research characteristics and hotspots of OLIF. Method: Searching the Web of Science database yielded the 50 most cited publications in the OLIF field as of July 10, 2022. The publications were ranked according to the number of citations. The following sources were evaluated: the year of publications, the number of citations, authors, countries, institutions, journals, research topics, and keyword hotspots. Results: The most productive period was from 2017 to 2020, with 41 articles. The number of citations varied from 10 to 140, with an average of 35.52, and 1,776 citations were found. World Neurosurgery published the most articles (12), China produced the most articles (16), and the Catholic University of Korea produced the most studies (6). The corresponding author who produced the most articles was J.S. Kim (5), and the first author who produced the most publications was S. Orita (3). The main research topics were anatomical morphology, surgical techniques, indications, outcomes, and complications. The top 10 most cited keywords were “complications,” “decompression,” “spine,” “surgery,” “outcomes,” “transpsoas approach,” “spondylolisthesis,” “anterior,” “disease,” and “injury.” Conclusions: Certain articles can be distinguished from others using citation analysis as an accurate representation of their impact due to their long-term effectiveness and peer recognition. With these publications, researchers are provided with research priorities and hotspots through influential literature in the field of OLIF.